African Statistical Yearbook 2016 - United Nations Economic Commission for Africa (United Nations, 2017)
The African Statistical Yearbook 2016 is the eighth edition jointly produced by the African Development Bank (AfDB), the African Union Commission (AUC), and the United Nations Economic Commission for Africa (ECA). As with the previous seven editions, this 2016 edition presents a time series showing how African countries performed on several economic and social indicators over the period 2007-2015. It is published consisting of two parts: a set of summary tables followed by country tables. The yearbook continues to serve the intended purpose of bringing together, in one volume, data on African countries for policy-makers, researchers and other users.